Enhanced flexibility of polylactic acid/epoxidized palm oil/pineapple fiber composites - Mohamad, Nur Lisa Farhana; Ali, Fathilah; Azmi, Azlin Suhaida; Barre, Mohamed Soleiman; Anuar, Hazleen; Jamaluddin, Jamarosliza (Kulliyah of Engineering, International Islamic University Malaysia (IIUM), 2020)
The concern about our dependency on non-renewable resources and overwhelming environmental issues such as pollution caused by non-degradable packaging materials has prompted researchers to come up with alternatives to solve this problem. Thermoplastic polylactic acid (PLA) has been gaining interest due to its versatility and easy processability, thus this study was carried out to find out the properties of PLA reinforced with pineapple fibers. However, surface of the natural fibers need to be treated for better properties enhancement in the polymer matrices. Considering this, fibers were treated with 10% (w/v) concentration of potassium hydroxide (KOH) and then continued for mixing with PLA at a fixed ratio of plasticizer by using internal mixer, and then the composites were prepared into sheet via hot press. Characterization for the mechanical and morphological was conducted by using tensile testing and scanning electron microscopy, respectively. After the analysis, it is found that the surface treated pineapple fiber composite showed better elongation at break compared to untreated fiber composite. The enhance properties of PLA nanocomposites has potential to be used in various packaging materials.